Family dysfunction, parenting stress, and child mental health: associations with bullying involvement and the moderating role of neighborhood support - Zhou, Qianyu; Lin, Chaohui; Guo, Xiang (Frontiers in Psychology, 2025)
IntroductionChildhood bullying is widespread and closely tied to family stress and mental health problems. When family relationships are strained and parents experience high stress, children’s psychological well-being may erode, increasing their chances of bullying involvement as aggressors or victims. This study assessed (1) whether family dysfunction (FD) affects bullying through a sequential pathway of parental aggravation (PA)—a marker of parenting stress—and children’s mental health (CMH), and (2) whether perceived neighborhood support (NS) tempers this chain.MethodsWe used data from the 2020–2023 National Survey of Children’s Health, a pooled cross-sectional, nationally representative sample totaling roughly 114,639 U. S. children aged 6–17 years. Primary measures were a composite FD index, a four-item PA scale, parent-reported CMH difficulties, perceived NS, and past-year bullying involvement. A moderated serial-mediation model tested the indirect pathway from FD to BI via parenting stress and CMH, with NS specified as a moderator.ResultsHigher levels of FD predicted greater PA and poorer CMH. Both parenting stress and child mental health difficulties were, in turn, associated with higher odds of BI. Serial mediation analysis supported a significant indirect effect of FD on BI through parenting stress and CMH. This mediated pathway was significantly weaker at high NS levels, indicating a buffering role.DiscussionFindings suggest that nurturing neighborhood environments can offset some of the negative consequences of FD and parental stress on children’s involvement in bullying. Prevention initiatives that simultaneously strengthen family functioning and neighborhood cohesion may therefore effectively curb youth bullying.